Variasi Dimensi Pipa Kapiler Sebagai Katup Ekspansi Terhadap Laju Pendinginan Pada Mesin Pendingin LUCAS NULLE TIPE RCC2 - Reki Karangan; Frans Palobo Sappu; Irvan Rondonuwu (JURNAL POROS TEKNIK MESIN UNSRAT, 2018)
One component of the cooling engine that plays an important role in the reducing temperature and refining pressure is the expansion valve.This research is fair to know the rate of cooling and elecricity consumption of a T2 type thermostatic expansion valve and a capillary pipe with a constant legth of 2 m with a diameter of 0,028 inches and 0,036 inches using the Lucas Nulle Type RCC2 cooling machine. The value of the result is obtained from three experiments for each tool for one hour.Based on the observations it was found that the average cooling rate using a T2 type thermostatic expansion valve can achieve a temperature decrease of up to 2,87 oC with an electricity consumption of 201,96 watts, for each capler using a 0,028 inch diameter decrease in temperature can reach up to -0,33 oC with electricity consumption of 198,22 watts and for the use of 0,036 inch diameter capillary pipe the temperature decreases can reach up to 5,37 oC with electricity consumption of 211,31 watts.Â Key word : T2 type thermostatic expansion valve, capillary pipe